2020
DOI: 10.3390/nu12020587
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Maternal Education for the Complementary Feeding of Undernourished Children Under 3 Years of Age in Food-Secure Communities: Randomised Controlled Trial in Urmia, Iran

Abstract: The mothers’ nutritional literacy is an important determinant of child malnourishment. We assessed the effect of a smartphone-based maternal nutritional education programme for the complementary feeding of undernourished children under 3 years of age in a food-secure middle-income community. The study used a randomised controlled trial design with one intervention arm and one control arm (n = 110; 1:1 ratio) and was performed at one well-child clinic in Urmia, Iran. An educational smartphone application was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…A total of six articles are included in this scoping review [ 13 , 14 , 15 , 16 , 17 , 18 ]. The total number of participants included in the studies was 4016 and the median study size was equal to 224 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of six articles are included in this scoping review [ 13 , 14 , 15 , 16 , 17 , 18 ]. The total number of participants included in the studies was 4016 and the median study size was equal to 224 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in the review reflected a broad heterogeneity of interventions: face to face training, class education and class simulation, in-person sessions with technology components, teaching laboratory through science engagement, and a classroom-based curriculum. Two [ 17 , 18 ] of the six interventions were devoted to infants (0–36 months) through mothers, and the rest to adolescents (11–17 years). The duration of interventions ranged from 4 to 16 weeks and outcomes were measured at two time points: at baseline and after the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reviewed the importance of social networks’ causal effects on health behaviors. The use of a collaborative setting among the interested parties such as social networks could enhance individuals’ motivation and skills for adopting healthy behaviors [ 8 , 44 – 46 ]. The findings of some review studies on educational apps for nursing mothers also indicated that social support, which is underdeveloped in many of the applications, is a major influencing feature on breastfeeding duration [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of health education programs greatly contributes to promoting maternal breastfeeding knowledge, attitude, and practice (KAP) [ 6 8 ]. Parents’ education is associated with an awareness of proper child-rearing practices, better health-seeking attitudes, improved knowledge about breastfeeding/complementary feeding, and up-to-date information about immunization [ 8 , 9 ]. By conducting four 60-min sessions of an educational program, Kang et al reported remarkable improvement rates in breastfeeding empowerment and practice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 12 With the increasing global prevalence of mobile phones, mHealth programmes have the potential to bring health content directly to millions of people through audio or text messages on their phones. Despite their proliferation, there is only limited evidence that mHealth interventions can improve aspects of routine health behaviour 13 and can specifically enhance child feeding 14 15 and contraception use. 16 There is little known about engagement with mHealth messages by the user (e.g., who listens, whether messages are discussed) and how users comprehend and reconcile the messages in relation to their own ongoing practices, perspectives, and social worlds.…”
Section: Introductionmentioning
confidence: 99%